Cetuximab in the treatment of advanced colorectal cancer– second line therapy - Szczylik, Cezary; Wcisło, Gabriel (Contemporary Oncology/Współczesna Onkologia, 2006)
The global morbidity and mortality due to colorectal represent 875 K new cases and 570 K deaths per annum, respectively. A human population affected by colorectal cancer embraces residents of the West or others but with their style of life accepted. Molecular investigations have shown the particular genes to have an influence on the development and progression of colorectal cancer, and the huge part of the cases are sporadic. Although, there have been known genetic syndromes in which colorectal cancer is a well-defined part each of them. New drugs in the therapy for advanced metastatic colorectal cancer will come from the basic research on the disease. An activated EGFR plays a pivotal role in development and progression of colorectal cancer, and evidence has accumulated that the molecule is considered a negative prognostic factor. Blocking monoclonal antibodies offers a new entity to treat advanced disease in order to hamper its progression. Cetuximab is exactly this EGFR blocking monoclonal antibody used in patients after completed palliative chemotherapy just irinotecan-resistant. The combination of irinotecan and cetuximab has offered approximately 19-23% overall response rate, and time to progression has been noted as 4 months, and overall survival has been presented over 8 months. Cetuximab is approved by the European Union (in Poland as well) for the treatment of advanced metastatic colorectal cancer together with irinotecan as the second-line palliative therapy in patients whose colorectal cancer progressed at the time of irinotecan infusions.